Sams teach yourself HTML in 10 minutes - Hayes, Deidre (Sams, 2006)
Don't let a lack of free time keep you from learning HTML to build better websites! Sams Teach Yourself HTML in 10 Minutes, Fourth Edition is a compact, task-oriented tutorial that will show you how to perform the most common tasks involved in designing, creating, publishing, and administering web pages and sites. The book covers only those HTML tags and technologies that are likely to be used on a beginner's web page, and it is organized in a logical step-by-step order that reflects a natural progression. The book's modular design allows you to jump in and learn only what you need to know anywhere throughout the book. This fourth edition of the bestselling book is completely rewritten to make it even more accessible for the beginning Windows and Macintosh user. The easily accessible reference material and updated examples will help understand how to execute tasks to get the results you desire.